HUBUNGAN KARAKTERISTIK INDIVIDU DAN PEMAKAIAN ALAT PELINDUNG DIRI (APD) DENGAN KADAR TIMBAL (Pb) DALAM DARAH PADA PEKERJA PENGECATAN DI INDUSTRI KAROSERI - Mayang Puspita Sari; Onny Setiani; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2016)
The painting section of karoseri industry gives potential lead exposure to workers. This is caused by the lead content that is used as a paint pigment and dryer. The use of unstandarized PPE by the workers can cause lead entering the body through respiratory tract which can cause bad impacts to the human health. The aim of this research was to analyze the association between individual characteristic such as age, duration of working hours, smoking habits and use of PPE to the levels of lead in blood and the type of research used was observational with cross sectional design. The population in this research was 53 people with a total sample of 32 respondents, which was obtained by using purposive sampling technique. The data analysis performed as univariate and bivariate with chi square test. The research results obtained were variables associated with lead content level in blood is smoking habits (p = 0.039) and the use of PPE bye the workers (p = 0.038). Variables that has unsignificant association were age (p = 1.000) and duration of working hours (p = 1.000). The conclusion of this research is that there is a connection between smoking habits and use of PPE by the workers with lead content level in blood on workers of painting section of Karoseri industry.